Pharmacotherapeutics applications and chemistry of chalcone derivatives - Dhaliwal, Jagjit Singh; Moshawih, Said; Goh, Khang Wen; Loy, Mei Jun; Hossain, Md Sanower; Hermansyah, Andi; Vijay, Kotra; Kifli, Nurolaini; Goh, Hui Poh; Sodhi Dhaliwal, Sachinjeet Kaur; Pg Hj Md Yassin, Hayati; Ming, Long Chiau (MDPI, 2022)
Chalcones have been well examined in the extant literature and demonstrated antibacterial, antifungal, anti-inflammatory, and anticancer properties. A detailed evaluation of the purported health benefits of chalcone and its derivatives, including molecular mechanisms of pharmacological activities, can be further explored. Therefore, this review aimed to describe the main characteristics of chalcone and its derivatives, including their method synthesis and pharmacotherapeutics applications with molecular mechanisms. The presence of the reactive α,β-unsaturated system in the chalcone’s rings showed different potential pharmacological properties, including inhibitory activity on enzymes, anticancer, anti-inflammatory, antibacterial, antifungal, antimalarial, antiprotozoal, and anti-filarial activity. Changing the structure by adding substituent groups to the aromatic ring can increase potency, reduce toxicity, and broaden pharmacological action. This report also summarized the potential health benefits of chalcone derivatives, particularly antimicrobial activity. We found that several chalcone compounds can inhibit diverse targets of antibiotic-resistance development pathways; therefore, they overcome resistance, and bacteria become susceptible to antibacterial compounds. A few chalcone compounds were more active than conventional antibiotics, like vancomycin and tetracycline. On another note, a series of pyran-fused chalcones and trichalcones can block the NF-B signaling complement system implicated in inflammation, and several compounds demonstrated more potent lipoxygenase inhibition than NSAIDs, such as indomethacin. This report integrated discussion from the domains of medicinal chemistry, organic synthesis, and diverse pharmacological applications, particularly for the development of new anti-infective agents that could be a useful reference for pharmaceutical scientists.